Adverse Effects of Androgen Deprivation Therapy for Prostate Cancer: Prevention and Management. (25th July 2013) - Sountoulides, Petros; Rountos, Thomas
Abstract : The prostate is an androgen-dependent organ. The increase, growth, homeostasis, and function of the prostate largely depend upon the intraprostatic and serum concentrations of androgens. Therefore, androgens are essential for the physiologic growth of prostatic epithelium. Prostate cancer, the second leading cause of death for men, is also androgen dependent, and androgen suppression is the mainstay of treatment for advanced and metastatic disease. In the state of metastatic disease, androgen suppression is a palliative treatment leading to a median progression-free survival of 18–20 months and an overall survival of 24–36 months. Theoretically, the majority of patients will develop hormone-refractory disease provided that they will not die from other causes. Although androgen suppression therapy may be associated with significant and sometimes durable responses, it is not considered a cure, and its potential efficacy is further limited by an array of significant and bothersome adverse effects caused by the suppression of androgens. These effects have potentially significant consequences on a variety of parameters of everyday living and may further decrease health-related quality of life. This review focuses on the aetiology of these adverse effects and provides information on their prevention and management.